Convicts’ Subjective Worldview vs Planning One’s Future (Archives of Criminology, 2017)
The prison, as a place of detention, has a number of tasks to achieve, one of the crucial ones being to rehabilitate the inmates, i.e. habituate them to life in basic social groups and institutions. The pursuit of this mission makes it necessary to maintain, construct or reconstruct non-existent, broken or dysfunctional social ties, including family ones. The primary goal of the penitentiary rehabilitation process is for the activities that inmates are involved in while serving their sentences to be conducive to taking up appropriate social roles while satisfying their needs in accordance with accepted values, models and social norms. A permanent change of behaviour can only be brought about if preceded by a cognitive change in the inmate’s system of beliefs and mentality. According to the cognitive theory of human behaviour, man’s actions are conditioned by information, while the structure of the information people have internalised determines what aims they pursue and what they avoid. Information comes from two primary sources – from the individual’s environment and from experience. It makes up every person’s subjective worldview and to large extent determines his or her actions. The article presents the findings of research conducted on a group of nine inmates regarding how they planned their future in light of their subjective worldview. The research was conducted in the form of individual, unlimited (time) interviews with the prisoners. The overarching aim was to find out what factors shaped the inmates’ subjective worldview and how the latter translated into what they were planning to with their future after leaving prison. Family and family relationships are one of the key elements that determine how inmates perceive the world. It is with family in mind – as the findings indicate – that inmates formulate their future goals. It is worth noting that the inmates’ approach to planning had changed in the course of serving their sentences – they currently see planning as a value and a condition of a successful return into the open. They shift their attention from the past to the future, they no longer concentrate only on their ‘old’ experiences, traumas and hurts, but begin increasingly to focus on the future and the present. They are critical of their former (pre-imprisonment) lifestyle and the decisions made then. They also distance themselves from their former crime partners, who have abandoned them. Hence, basic therapeutic and psycho-educational work with inmates should be based on the principles of cognitive-behavioural psychology. Using their declared willingness to change, we can raise the effectiveness of rehabilitation. Strong unwillingness to take part in therapeutic programs is a widespread problem in rehabilitation work. Hence, diagnosing or analysing individual perceptions of reality, and particularly the factors that underlie their specificity, is a key factor in bringing about change. Making plans requires looking at one’s past and present life from a different perspective. Imprisonment provides such a new perspective which, in spite of the hardships of detention, can also inspire reflection. For this to happen, the staff needs to be engaged in new programmes and methods of working with inmates. Raising one’s professional competence and increasing the number of one-on-one meetings with a psychologist and/or therapist are only some of the possible solutions prison staff can undertake. Another important element in the process of planning is time: the time already spent in prison and the time remaining until the end of the sentence. The least planning, as research indicates, is done by people who have just begun serving their sentence or who still have a lot of time ahead until release. Of course this does not mean that they do not think about their future life upon leaving the penitentiary facility. It is too great an emotional strain for these prisoners, however, they therefore focus on adapting to the new conditions in the best way possible from the viewpoint of potential gains. In the studied group, planning also coincided with a marked tendency to change, which cannot be achieved without the active support of inmates’ families. Hence it is also important to get the family circle involved the rehabilitation process. It is no easy task, yet doable, as shown by numerous programmes implemented in penitentiary facilities (such as ‘Daddy behind the wall’) which particularly today need to be innovative and adapted to the present.